Quantitative and qualitative changes in substance-related administrative offences in road traffic during the SARS-CoV-2 pandemic in Munich - Anna Holzer; Andreas Stoever; Michael Lau; Sabine Gleich; Matthias Graw; Anouk Ludwig; Benno Hartung (PLoS ONE, 2025)
Introduction The SARS-CoV-2 pandemic beginning in 2020 led to significant restrictions on social life and mobility, raising concerns about increased substance use across the general population. To investigate whether the pandemic resulted in quantitative or qualitative changes in alcohol and/or drug use in the context of road traffic, a retrospective analysis of toxicological findings was conducted in the city of Munich, considering the local pandemic-related restrictions. Materials and methods A total of 6,210 blood samples were analyzed from individuals suspected of committing substance-related administrative traffic offences under §24a of the German Road Traffic Act between January 1, 2019, and July 31, 2021. Samples were examined for the presence of substances, their concentrations, and the type of vehicle involved. The cohort was stratified into pre-pandemic and pandemic periods, with March 16, 2020 set as the cut-off date. The pandemic period was further subdivided based on the severity of imposed restrictions. Statistical comparisons were performed using Fisher’s exact test, t-tests, ANOVA, and logistic regression. Results Cannabis was the most frequently detected substance (66.2% pre-pandemic; 67.4% during the pandemic), followed by alcohol (11.7% vs. 10.8%) and cocaine (5.7% vs. 5.2%). Only minor differences were observed between the pre-pandemic and pandemic periods, as well as across phases of mild versus severe restrictions. Notably, THC-COOH concentrations were higher during the pandemic. Alcohol levels were elevated during phases of light restrictions and reduced during periods of strict lockdown. Cannabis was most commonly detected in car drivers, whereas alcohol was more frequently found in e-scooter riders, particularly during less restrictive phases. Conclusion Substance detection patterns among drivers in Munich showed overall stability during the COVID-19 pandemic, with cannabis remaining the most commonly identified drug. However, shifts in substance concentrations and differences by vehicle type and restriction severity suggest subtle changes in consumption behavior. These findings underscore the need for continued surveillance and context-specific traffic safety measures.